Pengujian Respon Hasil Inokulasi Tanaman Gaharu (Aquilaria malaccensis) pada Berbagai Volume Inokulan dan Jarak Antar Lubang Inokulasi - Kusumaningsih, Kartirahayu; Rawana; Asmita, Fika (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2022)
Agarwood is one of non wood forest products that has very good prospect to be developed. Right now, the market demand of agarwood products is become more increasing, so study of artificial agarwood production is necessary to be expanded. At process of agarwood plant inoculation, the suitable inoculant with proper volume and distance between inoculation holes, will effect against inoculation result. Purpose of this study were to know effect of inoculant volume and distance between inoculation holes against response of Aquilaria malaccencis after three month inoculated. Results of the research showed that percentage of inoculation success at A. malaccensis that inoculated with 2,5 ; 5 and 7,5 ml inoculant volume and distance between inoculation holes 5 x 5 and 10 x 10 cm were 100%, its meaned all inoculated plant were infected with fungus. Inoculant volume did not give significant effect against length of fungal infection, but there was tendency that 7,5 ml inoculant volume resulted higher length of fungal infection than 2,5 ml and 5 ml volume. The distance between inoculation holes 5 x 5 cm resulted higher length of fungal infection than 10 x 10 cm, i.e 7.82 cm and 1.89 cm. Fragrance level of Aquilaria malaccensis inoculation result after 3 months inoculated was classified in the fragrant criteria. Keywords : distance between inoculation holes; inoculant volume; test response